ASSISTANCE IN MANUFACTURING SOAP FROM CITRAI AS AN ECONOMIC SOLUTION FOR THE USE OF HOUSEHOLD INGREDIENTS IN WATUMANU BAJAWA VILLAGE - Amrin, Sayful; Parera, Helena Rosalia; Ota, Maria Kristina; Nande, Marsel; Ma, Stefanus Hubertus Gusti; Ngapa, Yulius Saprianus Dala; Banda, Yosef Moan; Tola, Damianus; Djou, Anna Maria Gadi; Nino, Oktavianus (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
This article explains the activities carried out in Watumanu village, Ngada district; the activities of utilising household materials to be processed into soap are carried out with the village community as partners. The geographical conditions of the land are fertile, and people who use their yards to grow household materials routinely use them for daily consumption. This training assistance aims to provide breakthroughs, knowledge for innovation, and the creation of new products for village communities that make soap from lemongrass. The soap products can become a mainstay for Bumdes and can be used daily to save on household expenses. By using household materials, apart from saving expenses, they can also be sold to increase people's income.